Late Pleistocene glacial fluctuations in Cordillera Oriental, subtropical Andes - Martini, Mateo Antonio; Kaplan, Michael R.; STRELIN, Jorge Adrián; Astini, Ricardo Alfredo; Schaefer, Joerg M.; Caffee, Marc W.; Schwartz, Roseanne (Quaternary Science Reviews)
The behavior of subtropical glaciers during Middle to Late Pleistocene global glacial maxima and abrupt climate change events, specifically in Earth´s most arid low-latitude regions, remains an outstanding problem in paleoclimatology. The present-day climate of Cordillera Oriental, in arid northwestern Argentina, is influenced by shifts in subtropical climate systems, including the South American Summer Monsoon. To understand better past glacier-subtropical climates during the global Last Glacial Maximum (LGM, 26.5–19 ka) and other time periods, we combined geomorphic features with forty-two precise 10Be ages on moraine boulders and reconstructed paleo-equilibrium line altitudes (ELA) at Nevado de Chañi (24°S) in the arid subtropical Andes. We found a major glacial expansion at ∼23 ± 1.6 ka, that is, during the global LGM. Additional glacial expansions are observed before the global LGM (at ∼52–39 ka), and after, at 15 ± 0.5 and 12 ± 0.6 ka. The ∼15 ka glacial event was found on both sides of Chañi and the ∼12 ka event is only recorded on the east side. Reconstructed ELAs of the former glaciers exhibit a rise from east to west that resembles the present subtropical climate trajectory from the Atlantic side of the continent; hence, we infer that this climate pattern must have been present in the past. Based on comparison with other low-latitude paleoclimate records, such as those from lakes and caves, we infer that both temperature and precipitation influenced past glacial occurrence in this sector of the arid Andes. Our findings also imply that abrupt deglacial climate events associated with the North Atlantic, specifically curtailed meridional overturning circulation and regional cooling, may have had attendant impacts on low subtropical Southern Hemisphere latitudes, including the climate systems that affect glacial activity around Nevado de Chañi. Fil: Martini, Mateo Antonio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de ...